Analysis Of Financial Ratios and Company Size As Determining Factors For Islamic Social Reporting Disclosure In Sharia Banks In Indonesia (Period 2015-2020) - Taufiq, Maf'ul (Mahesa Research Center, 2024)
This study investigates the determinants of Islamic Social Reporting (ISR) disclosure among Islamic banks in Indonesia from 2015 to 2020. Using financial ratios (ROA, CR, DER) and firm size as factors, the research explores their impact on the extent of ISR disclosures. The study employs quantitative analysis based on data from annual reports of Indonesian Islamic banks, applying regression models to test hypotheses derived from stakeholder theory, legitimacy theory, and resource dependency theory. The findings reveal that profitability and liquidity positively influence ISR disclosures, indicating that more profitable and liquid banks are more likely to engage in and report on social responsibility activities. In contrast, leverage shows a negative relationship with ISR disclosures, suggesting that highly leveraged banks disclose less about their social initiatives. Additionally, firm size positively correlates with ISR disclosures, highlighting that larger banks tend to provide more comprehensive reports on their social responsibilities. Theoretical implications suggest that Islamic banks strategically manage their financial and organizational resources to enhance legitimacy and stakeholder trust through transparent ISR disclosures. Practical implications underscore the importance of integrating CSR practices into business strategies to promote sustainability and accountability. The study contributes to the literature by providing empirical insights into ISR practices in Islamic banking and informs stakeholders about the factors influencing social responsibility disclosures.